THE FUTURE OF GREEN HOUSEHOLD APPLIANCES: CONSUMER PREFERENCES, MARKETING TOOLS AND CHALLENGES WITH SUSTAINABILITY GOALS - Shah, Heer; Chauhan, Vilas (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The future of green household appliances is poised at the intersection of consumer preferences, innovative marketing strategies, and the growing urgency to meet sustainability goals. As environmental awareness rises globally, consumers are increasingly favouring energy-efficient, eco-friendly appliances. However, the shift in consumer behaviour is driven not just by ecological concerns but also by cost savings and performance efficiency, pushing manufacturers to innovate beyond traditional offerings. This paper explores behavior pattern of consumers in relation to various appliances. It aims to understand consumers’ perception and reasons for purchasing Eco-friendly products. The study further delves to explore the relationship between Green Marketing Tools and Green Purchase Behavior as well as it explores the relationship between consumer’s attitude towards Sustainable Development Practices. This paper seeks to provide a comprehensive overview of the future trajectory of green household appliances, highlighting the delicate balance between, marketing tools and strategies, and the challenges involved in achieving global sustainability objectives.